Study of motivating and stressful facts in basketball atlhetes of the adult male national championship - Luciane Cristina Arantes da Costa; Lenamar Fiorese Vieira (Journal of Physical Education (Maringá), 2008)
This descriptive study aimed at investigating the motivating and stressful facts concerning the basketball athletes of the Adult Male National Championship of 2002. Eighty seven (87) athletes who integrated eight (08) teams were subjects of this study. The semi-structural interview and Frester’s Psychic Load Test (1972, apud SAMULSKI, CHAGAS, 1992) were used as measure instruments. The descriptive statistics and the content analysis by “cuts” were used for data analysis. The findings showed that the facts considered as motivators during the competition were: the audience, the fact of constantly thinking on achieving the desirable aims, and the establishment of very high aims; the stressful factors were: to be prejudiced by the referees, disagreements and conflicts with the coach, partners and family, and the sensation of physical weakness. Therefore, we can conclude: the facts that influence the interest can be of motivating or stressful order, depending on the personal and situational perception. Evaluation seems to be influenced by both the subject own personality and the social system.